A Ruse by Any Other Name: Comparing Loot Boxes and Collectible Card Games Using Magic Arena - Mattinen Topias; Macey Joseph; Hamari Juho (Association for Computing Machinery, 2025)
The convergence of gaming and gambling, known as "gamblification", has been a topic of increasing interest in recent years. Loot boxes, i.e., rewards ofering randomized content in exchange for money or time, have been a particular focal point. Research has shown links between excessive loot box consumption and problematic consumption behaviors, leading to several atempts to regulate loot boxes. Arguments against regulation have been that loot boxes are conceptually and structurally akin to other unregulated game formats, such as collectible card games. However, this discourse is oven without deeper analysis of the mechanics of diferent products at the center of convergence. |erefore, to add to this knowledge, this article examines the similarities and diferences between booster packs in Magic Arena, their physical counterparts in Magic: |e Gathering, and loot boxes included in digital games. Particular atention is paid to the ways in which these booster packs compare to loot boxes in terms of consumption paterns, visual appearance, contextual factors, and regulation. Analysis reveals that digital booster packs in Magic Arena difer from both loot boxes and physical card packs, both due to their direct impact on gameplay, and their unique features aforded by the digital environment in which they exist.